Optimizing solar panel output by using light sensors, driving motors and fuzzy controller. (April 2019) - Ilham, Dirja Nur; Fadhila, Fifi; Nababa, Erna B.; Suherman,; Candra, Rudi Arif
Abstract: Indonesia has limited electricity supplies and often experience blackout. On the other hand, this country is rich with sunlight. Sunlight is always available for the entire year due to the tropical weather and earth position is near to Equator. However, solar cell usage is still limited to be applied. This paper presents solar panel controller design to maximize the power output by using light sensors, two driving motors and fuzzy logic controller. The prototype is modelled and simulated based on measured data. Simulations have been made between the designed systems versus static system. The recorded data shows that by controlling solar panel following the position of the sun, the power output increases about 15.69 % over the static system.